A Moderating Role of Board Characteristics on Enterprise Risk Management Implementation: Evidence from the Nigerian Banking Sector - Dabari, Ishaya John; Saidin, Siti Zabedah (International Journal of Economics and Financial Issues, 2016)
The objective of this study is to examine the extent of ERM implementation in the Nigerian banking sector and also evaluated the moderating role of board characteristics on the antecedents and the stage of ERM implementation. The study used a survey approach to collect cross-sectional data across 361branches and the headquarters of the 21 Nigerian commercial banks using 722 respondents. The finding revealed that there is an ERM complete in place in the majority of the banks. Furthermore, the finding showed that internal audit effectiveness, human resource competency and top management commitment effect significant influence on the stage of ERM implementation, and there is also a moderating effect of board characteristics on internal audit effectiveness and the stage of ERM implementation. The paper has a policy implication for the board of directors to improve their oversight functions and the regulatory authorities to entrench risk-based supervision in all the Nigerian banks. Keywords: board characteristics; enterprise risk management; Nigerian banks; shareholder value. JEL Classifications: M41, M48